2020
DOI: 10.4103/joco.joco_113_20
|View full text |Cite
|
Sign up to set email alerts
|

Delhi Infectious Keratitis Study

Abstract: Purpose: To study the clinico-microbiological profile and outcomes of infectious keratitis (IK) at a tertiary eye care center in North India. Methods: This is a retrospective, hospital-based, cross-sectional study. One thousand seven hundred and eighty-six corneal microbiological reports were identified from January 2017 to December 2018, out of which 625 patients of IK fulfilled the inclusion criteria. They underwent microbiological examination which included corneal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 21 publications
3
16
2
Order By: Relevance
“…showed among bacteria's Staphylococcus was major gram-positive organism isolated followed by Streptococcus, which was the common pattern of growth seen all over India as well in our study. [11][12][13][14] In our study we found 47.7% of organism were gram positive cocci, study conducted by Gopinathan [15][16][17] In the present study majority of the Fungus isolated were like Aspergillus and Fusarium, it was observed that a study conducted by Lin CC et al showed prevalence of Aspergillus and Fusarium were common among southern region of India due to hot and windy climate. 18…”
Section: Discussionsupporting
confidence: 58%
“…showed among bacteria's Staphylococcus was major gram-positive organism isolated followed by Streptococcus, which was the common pattern of growth seen all over India as well in our study. [11][12][13][14] In our study we found 47.7% of organism were gram positive cocci, study conducted by Gopinathan [15][16][17] In the present study majority of the Fungus isolated were like Aspergillus and Fusarium, it was observed that a study conducted by Lin CC et al showed prevalence of Aspergillus and Fusarium were common among southern region of India due to hot and windy climate. 18…”
Section: Discussionsupporting
confidence: 58%
“…Out of these 157 patients, 112 (71.34%) were male and 45 (28.66%) were female, and the average age of the patients undergoing TPK was 54.01 years (range, 12–85 years). As already mentioned in the article, 1 corneal button culture yielded bacterial growth in 66 cases (42.04%) and fungal growth in 47 cases (29.94%), and 44 cases (34.65%) yielded no growth.…”
supporting
confidence: 61%
“…This communication is a continuation of the article titled “Delhi infectious keratitis study: Update on clinico-microbiological profile and outcomes of infectious keratitis” published in the previous edition of your Journal. 1 In the aforementioned article, 1 we had presented the microbiological profile of infectious keratitis along with the antimicrobial sensitivity pattern, and we would like to provide supplemental information about the 157 patients in the study who underwent therapeutic penetrating keratoplasty (TPK), with regard to their anatomical and visual outcomes postsurgery. Out of these 157 patients, 112 (71.34%) were male and 45 (28.66%) were female, and the average age of the patients undergoing TPK was 54.01 years (range, 12–85 years).…”
mentioning
confidence: 99%
“…Bacterial keratitis is the commonest form of infectious keratitis globally with incidence ranging from 50 to 60% ( 29 ). The potential risk factors for bacterial keratitis include contact lenses, aqueous tear deficiencies, trauma, decreased immunologic defenses, eyelid alterations or malposition, neurotrophic keratopathy, topical corticoid medications and surgery ( 30 ).…”
Section: Infectious Keratitis – Types Clinical Features and Managementmentioning
confidence: 99%
“…Incidence of HSV (Viral keratitis) and Acanthamoeba keratitis are 15-40% and 0-5% respectively ( 32 ). Also, mixed infections comprising of infliction by more than one organism is also seen in 2-15% of patients ( 29 ).…”
Section: Infectious Keratitis – Types Clinical Features and Managementmentioning
confidence: 99%